Nationalized industry and public ownership - Robson, William Alexander (Tornoto : University of Toronto Press, 1960)
This book is concerned with nationalized industry in Britain. The book consisted of several articles which had appeared in a special number of the political quarterly together with a larger number of new essays written specially for the book.
Includes bibliographical references p. 499-528 and index.
hza 02/08/2018
Loans
Keywords: Government ownership; Britain